Does Gamification Make a Difference in Programming Education? Evaluating FGPE-Supported Learning Outcomes - Jakub Swacha; Justyna Szydłowska (MDPI AG, 2023)
While gamification has been paired with computer programming education on numerous occasions, most of the scientific reports covering the evaluation of its learning outcomes pertain to single-case specialized gamification applications with none or little chance of reuse in other institutions and courses; thus, they offer only limited replicability and comparability of results. In this work, we aim to address this gap by investigating the learning outcomes of a programming course based on the FGPE (Framework for Gamified Programming Education) platform, an open-source, fully configurable gamification platform developed specifically to support teaching and learning computer programming that can be used by any institution to support any programming-related course. This is, to the best of our knowledge, the very first study evaluating the learning outcomes of FGPE-supported programming education. Moreover, we address the question of whether students learning with gamified platforms limited to programming practice can benefit from additionally using non-gamified MOOCs by comparing the results attained in three groups differing in the choice of learning support tools (FGPE and MOOC vs. FGPE only vs. MOOC only).